ABOUT ARTIFICIAL INTELLIGENCE - Joldasbaeva Ramuza Kuatbaevna; Djankhodjaev Nursultan (Web of Journals Publishing, 2025)
The components of AI include intellectual education, innovative virtual learning, analyzing data and identifying the learning-style, providing feedback for teachers and students is also made by AI.
Keywords: Artificial intelligence, innovations, education, computer, the quality of education.